(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda aims to prevent and cure diseases. In Ayurvedic system of medicine, bloodletting procedure is a kind of para-surgery practiced for the treatment of specifically blood borne diseases along with other surgical diseases. Therapeutic bloodletting is indicated in abscess, cellulitis, chronic ulcers resulting from snake bite, filariasis, genital infections, gout, herpes, inflammatory conditions, Skin disorders, tumors, ulcers, etc. While mentioning the five methods of body detoxification, the Ayurvedic texts mentions bloodletting as one among them, so it is one of the important therapies in Panchakarma. Bloodletting is also known as Phlebotomy and considered to be a prime treatment modality among the surgical procedures in Ayurveda. With curative aspects it also acts in preventive and promotive aspects. The vitiated impure blood is removed out from the body by the seven procedures - Venesection (Siravyadhana), scrapping (Pracchanna karma), horn application (Sringa avacharana), gourd application (Alabu avacharana), leech application (Jalauka avacharana), application of cupping pot/glass (Ghatiyantra avacharana), and needle application (Suchivyadhana). Bloodletting is also used to lower the iron levels and prevents its accumulation in various organs. Therapeutic bleed is a holistic treatment for impure blood and it helps to bring the body back into its natural and homoeostatic state.